Studying the effect of using some additives on changing azeotropic behavior in distillation - Ng, Wei Kuen (2008)
Absolute ethanol is an important product required by industry. Azeotropic chemical mixture such as ethanol-water is impossible to break up to its original composition by simple distillation. The separation of azeotropic mixtures via distillation is quite complex because at the azeotrope condition, liquid phase and gas phase have the same composition and, therefore, the driving force for distillation disappears. In order to study the effect of entrainer, four solvents are investigated which is cyclohexane, benzene, chloroform and acetonitrile. Type and composition of the entrainer were being the major variable under focus in the present investigated which will produce high concentration of ethanol. Each entrainer will be conducted with different composition in order to discover the optimum condition for breaking up the azeotropic mixture. The optimum composition to get high efficiency of ethanol for lst section of testing is at experiment 7, 2nd section of testing at experiment 7, 3rd section of testing at experiment 3 and 4th section of testing at experiment 1. The experiment result shows that in optimum composition of each additive; cyclohexane, benzene, chlomfonn and acetonitrile perform as additives in breaking up the azeotrope chemical mixture water-ethanol.